2003
DOI: 10.1111/j.1348-0421.2003.tb03404.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Infection in TLR2 and TLR6 Knockout Mice

Abstract: Abstract:To investigate the role of TLR in the development of murine tuberculosis in vivo, TLR2 and TLR6 knockout (KO) mice were infected with Mycobacterium tuberculosis by placing them in the exposure chamber of an airborne infection apparatus. Both TLR2 and TLR6 KO mice survived until sacrifice at 12 weeks after infection. Infected TLR2 KO mice developed granulomatous pulmonary lesions with neutrophil infiltration, which were slightly larger in size than those in wild-type mice. Pulmonary levels of the mRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(121 citation statements)
references
References 29 publications
4
114
1
2
Order By: Relevance
“…Further research into the innate immune response may elucidate pathological mechanisms underlying infectious morbidities such as tubal infertility and preterm labour, but as yet few studies have examined the functional effects of innate immune components such as NAPs and TLRs in the reproductive tract. While existing SLPI (Ashcroft et al 2000) and TLRnull (Sugawara et al 2003, Andersen-Nissen et al 2007) mutant mouse models show impaired wound healing and altered responses to infection, they have provided little information relating directly to the reproductive tract. In addition, fundamental differences in key physiological reproductive processes, such as implantation and placentation, exist between mouse and human limiting the relevance of these rodent models.…”
Section: Resultsmentioning
confidence: 99%
“…Further research into the innate immune response may elucidate pathological mechanisms underlying infectious morbidities such as tubal infertility and preterm labour, but as yet few studies have examined the functional effects of innate immune components such as NAPs and TLRs in the reproductive tract. While existing SLPI (Ashcroft et al 2000) and TLRnull (Sugawara et al 2003, Andersen-Nissen et al 2007) mutant mouse models show impaired wound healing and altered responses to infection, they have provided little information relating directly to the reproductive tract. In addition, fundamental differences in key physiological reproductive processes, such as implantation and placentation, exist between mouse and human limiting the relevance of these rodent models.…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophil depletion during early mycobacterial infection exacerbates disease and dysregulates granuloma formation (23)(24)(25)(26). However neutrophils are associated with tissue damage and necrosis in late disease and are a feature of granulomas in gene-deletion models associated with increased susceptibility to tuberculosis (27)(28)(29)(30)(31)(32)(33). Neutrophils release mediators that likely contributed to the angiogenesis in the trehalose mycolate-bearing matrices, evident at 4 days postinjection (34).…”
Section: Discussionmentioning
confidence: 99%
“…While some groups found that TLR-mediated signalling is dispensable for protective immunity against M. tuberculosis [3][4][5][6], others suggested an essential contribution of TLR to protection [7][8][9]. The TLR contain a Toll/IL-1 receptor domain, which associates with the adaptor molecule MyD88.…”
Section: Introductionmentioning
confidence: 99%